Identity Theft and Data Breaches How Stolen Data Circulates on the Dark Web: A Systematic Approach - Tayyba Jabeen; Yasir Mehmood; Hamayun Khan; Muhammad Fawad Nasim; Syed Asad Ali Naqvi (Spectrum of Engineering Sciences, 2025)
The dark web, part of the deep web, can be accessed only through specialized computer software and used for illegal activities such as cybercrime, drug trafficking, and exploitation. Technological advancements like Tor, bitcoin, and cryptocurrencies allow criminals to carry out these activities anonymously. Identity theft and data breaches are becoming considerable issues with the rapid growth in the technological world such as the dark web marketplace. This study explores some high-profile data breaches like Equifax and Anthem. Also included the financial impact of stolen data or data breaches on individuals as well as organizations. Furthermore, this article demonstrated the role of the dark web in selling stolen data. The stolen data could be a person’s personal information such as name, email address, credit card details and social security number. Different data circulation approaches are discussed in this article like dark web marketplaces and forums. Cryptocurrency is being used for the transactions for such selling, because of its anonymity feature which a typical currency can not provide. This research also demonstrated the role of cyber security and laws such as GDRP and CCPA. Keywords: Dark Web, Identity Theft, Stolen Data, Data Circulation on Dark Web, Data Breaches, Cyber Security